2012
DOI: 10.1142/s1793292012300058
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Suitable Method for the Synthesis of Copper Nanoparticles

Abstract: Various methods for the synthesis of copper nanoparticles employing chemical, physical and biological techniques considering bottom-up and top-down methods synthesis have been studied. The properties of copper nanoparticles depend largely on their synthesis procedures. The results from various investigations performed by di®erent scientists using these methods have been summarized. The applications, characterization techniques, advantages and disadvantages of each synthesis method are also the point of discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(106 citation statements)
references
References 146 publications
2
104
0
Order By: Relevance
“…Biological or biosynthesis [14] techniques are also considered as chemical methods. Cu NP has high thermal conductivity [15] and also the production cost is very low as compare to noble metals. Cu NP production using chemical reduction method gives good results but use of hazardous reducing and costly and protecting agent [16][17][18][19][20][21][22] makes the process toxic in some cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological or biosynthesis [14] techniques are also considered as chemical methods. Cu NP has high thermal conductivity [15] and also the production cost is very low as compare to noble metals. Cu NP production using chemical reduction method gives good results but use of hazardous reducing and costly and protecting agent [16][17][18][19][20][21][22] makes the process toxic in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the toxicity and to prepare Cu NP in green environment, we have used ascorbic acid in our chemical reduction process. Ascorbic acid works both as reducing and protecting agent, which makes the process economical, nontoxic and environment friendly [15]. The raw materials are the same as Jing Xiong [23]; however, the synthesis route and the equipments have been changed, which resulted in the size variation of NP in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that the limited bioavailability of many nanoparticles in aqueous environments occur due to their low solubility and tendency to accumulate leading to toxicity, and these substances can be toxic to many aquatic organisms (Piotrovskii and Kiselev 2006;Zuykov et al 2013). Among various nanoparticles, zinc nanoparticles are widely used in various fields due to their simple access, low cost and specific physical and chemical properties (Umer et al 2012;Fan et al 2017). Despite the large production and application of zinc nanoparticles, which its effluent consequently is being released into the environment, the information about the possible effects of these substances on living organisms is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, copper nanoparticles have been used with promising results as bactericides [20] [29].…”
Section: Introductionmentioning
confidence: 99%